Transformasi Pendidikan Islam di Indonesia Menuju Kesetaraan Dengan Pendidikan Umum - Sodik budiono; Khairuddin Khairuddin; Idil Fitri (Universitas 45 Surabaya, 2023)
The reform and renewal of Islamic education in Indonesia focus on enhancing its relevance to the needs of modern society as well as advancements in technology and science. Islamic education in Indonesia faces significant challenges in responding to rapid social changes and global competition, which demand innovation in educational approaches. The reform aims to integrate traditional Islamic values with 21st-century skills, such as critical thinking, creativity, and digital literacy. Efforts include revising the curriculum to be more inclusive, improving teacher quality, and applying competency-based teaching methods, enabling students to gain not only theological understanding but also practical skills applicable in various social and professional contexts. Additionally, integrating Islamic values into general education is strengthened to foster students with noble character, responsibility, and adaptability to global developments. The success of these reforms depends on the synergy between the government, educational institutions, the community, and other stakeholders to establish an Islamic education system that is both relevant and capable of addressing the challenges of the digital era and current moral crises. Moreover, these reforms are expected to contribute to fostering a balance between religious values and practical skills, ensuring students are well-equipped to navigate contemporary challenges. Thus, Islamic education reform in Indonesia is expected to produce highly competitive graduates who can positively contribute to national development and a more harmonious global civilization.